M. B. Коваль. Україна: 1939—1945. Маловідомі і непрочитані сторінки історії - Сушко, О. О.; Виговський, М. Ю. (Український історичний журнал, 2025)
M. B. Коваль. Україна: 1939—1945. Маловідомі і непрочитані сторінки історії. К., 1995. — 201 с.